Kyrgyz Republic : Ex Post Assessment of Longer-Term Program Engagement. (Policy Papers; Policy Paper ;, 2011)
This report reviews the Kyrgyz Republic's economic performance under Fund-supported programs from early 2005 to mid-2010. Two Fund-supported programs are assessed: the March 2005 Poverty Reduction and Growth Facility (PRGF, which expired in May 2008), and the December 2008 Exogenous Shock Facility (ESF, which expired in June 2010). Earlier Fund-supported programs were discussed in the Kyrgyz Republic's first Ex Post Assessment (EPA), which was completed in November 2004. The assessment does not cover performance under the Rapid Credit Facility (RCF), which was approved by the Executive Board on September 15, 2010.